Résurgences paysagères et nouvelles économies agricoles dans le périurbain francilien - Monique Poulot (Projets de Paysage)
Landscape and agricultural challenges have became so important into the space organization of a great metropolis such as Ile-de-France that new procedures, as the protected agricultural areas are now included in the planning urban actions. Such evolutions show a new will of a shared rural and urban planning, with, in the rural side, the preservation of a heritage landscape which is likely to formalise a high quality gateway to the city and the concern for a local and healthy food supply. The difficult invention of agri-urban raises three questions : a fisrt question about scales or the intervention areas ; a second one about the actors and their coalition ; a last one about the everyday practices on landscapes and their publicization.